Effects of a Health Education program on cognition, mood and functional capacity - Juliane Cristine Dias; Isabela Azevedo Rodrigues; Francine Golghetto Casemiro; Diana Quirino Monteiro; Bruna Moretti Luchesi; Marcos Hortes Nisihara Chagas; Paula Costa Castro; Sofia Cristina Iost Pavarini; Aline Cristina Martins Gratão (Revista Brasileira de Enfermagem)
ABSTRACT Objective: Assess the effect of a Health Education (HE) program on cognition, mood and functional capacity of participants in a University of The Third Age (U3A). Method: Controlled clinical trial. The HE Program consisted of 10 sessions with group dynamics, including orientations on disease prevention and cognitive stimulation exercises, lasting four months. Intervention Group (IG) n=13; and Control Group (CG) n=15. All were assessed at the start and end of the study, using Addenbrook´s Cognitive Examination-Revised (ACE-R), Beck Depression and Anxiety Inventory (BDI/BAI) and Functional Independence Measure (FIM). Results: Significant improvements were observed for the IG when comparing the total ACE-R score (p=0.001) and memory domain (p=0.011) before and after the intervention. For the CG, improvement was found in the memory domain only (p=0.027). Conclusion: a HE intervention program benefits the improvement in cognitive performance, particularly the memory of adults and active elderly who participated in a U3A.